Impact of the fuel mixture ratio of AVGAS 100LL and RON 92 fuel on combustion characteristics - Sabam Danny Sulung; Daniel Dewantoro Rumani; Ikhwanul Qiram; Muhammad Nur Cahyo Hidayat Nasrullah; Untung Lestari Nur Wibowo (Journal of Science Technology (JoSTec), 2023)
AVGAS 100LL is an aviation fuel used in piston engine aircraft, particularly in training aircraft such as the Cessna 172S with Lycoming engines. The use of lead in this fuel can have various health-related concerns. Therefore, reducing the use of leaded fuel has become a solution to address these issues. This study aimed to investigate the combustion characteristics of AVGAS fuels, including AVGAS 100%, AVGAS 75% + PERTAMAX 25%, and AVGAS 50% + PERTAMAX 50%. The research involved conducting combustion tests using a Bunsen burner. The results showed that the addition of PERTAMAX to AVGAS significantly influenced the temperature, color, flame height, and flame area produced. The temperature values were higher for AVGAS 100% compared to AVGAS mixed with PERTAMAX. On the other hand, the flame height and flame area were lower for AVGAS 100% compared to the blended fuels. These findings indicate that the addition of PERTAMAX affects the combustion characteristics of AVGAS fuels. Further studies are recommended to explore and expand our understanding of the effects of blending AVGAS with alternative fuels.